2019
DOI: 10.3390/nu11123005
|View full text |Cite
|
Sign up to set email alerts
|

High Oleic Acid Peanut Oil and Extra Virgin Olive Oil Supplementation Attenuate Metabolic Syndrome in Rats by Modulating the Gut Microbiota

Abstract: Unhealthy dietary patterns are important risk factors for metabolic syndrome (MS), which is associated with gut microbiota disorder. High oleic acid peanut oil (HOPO) and extra virgin olive oil (EVOO), considered as healthy dietary oil, are rich in oleic acid and bioactive phytochemicals, yet efficacy of MS prevention and mechanisms linking to gut microbiota remain obscure. Herein, we investigated HOPO and EVOO supplementation in attenuating diet-induced MS, and the potential mechanisms focusing on modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…Likewise, the consumption of olive oil (unsaturated fatty acids) negatively impacts the abundance of Corynebacteriaceae and of several families in the Firmicutes phylum while showing no influence on Bacteroidetes families. Several studies such as De Wit et al (2012) 56 , Zhao et al (2019) 57 and Farras et al (2020) 58 have reported associations between olive oil intake and a reduction in Firmicutes/Bacteroidetes ratio, consistent with the observations here. The NB-FAR model also suggests that Bifidobacteriaceae abundances are positively associated with grain intake ( vioscreen_hei_grain: Healthy Eating Index (HEI) Score of total grain), as previously observed 59 .…”
Section: Applicationsupporting
confidence: 90%
“…Likewise, the consumption of olive oil (unsaturated fatty acids) negatively impacts the abundance of Corynebacteriaceae and of several families in the Firmicutes phylum while showing no influence on Bacteroidetes families. Several studies such as De Wit et al (2012) 56 , Zhao et al (2019) 57 and Farras et al (2020) 58 have reported associations between olive oil intake and a reduction in Firmicutes/Bacteroidetes ratio, consistent with the observations here. The NB-FAR model also suggests that Bifidobacteriaceae abundances are positively associated with grain intake ( vioscreen_hei_grain: Healthy Eating Index (HEI) Score of total grain), as previously observed 59 .…”
Section: Applicationsupporting
confidence: 90%
“…Our results indicated that only the animals fed the diet enriched with saturated fat (butter) showed significantly higher values of body weight and adiposity (total visceral fat) compared to control and EVOO diets, although the EVOO diet contained the same energy density, and that no marked differences were recorded in food intake although a significant reduction in food intake was established in the butter diet at the end of the experimental period, probably as a response to the increase in body weight. This beneficial effect of olive oil in the regulation of body weight has been described in previous works [ 19 , 20 , 21 , 22 ] and could be related to the minor components included in the unsaponifiable fraction of EVOO [ 23 ] and gut dysbiosis [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 68%
“…Lachnospiraceae are the main producers of short-chain fatty acids (SCFAs) and have been associated with intestinal diseases (Vacca et al, 2020). They are also increased in obese subjects, which suggested that the metabolic syndrome may be related to a gut microbiota disorder (Zhao et al, 2019). The study of microbial excavation and interaction is useful to reveal the influence of heat stress on the intestinal mucosal barrier and can provide a theoretical basis and experimental ideas for the prevention and repair of body damage caused by heat stress.…”
Section: Discussionmentioning
confidence: 99%